Factores determinantes para as necessidades em saude das pessoas consumidoras de drogas: uma revisão bibliográfica - Seabra, Paulo (2011)
The provision of care aimed the health needs satisfaction has followed the practice and research in nursing. The health needs can be understood as essential to a better well-being, better functional ability and satisfaction enables a greater likelihood of sickness absence. The determinants of health needs arising from individual factors (genetic, biological, behavioural and psychological), environmental, economic, social and cultural. Are related to lifestyles throughout the life cycle. Are essential for assessing the health of populations. It is relevant to the relationship between needs and satisfaction as a right, and in this case, there may be no correlation between the perception of people about their needs and the nurses. We performed a literature review in order to identify the state of the art in regard to determining the health needs of people who consume drugs. We conducted a search in the databases scielo and b-on repositories of universities, as well as some specialized publications. We select studies on needs assessment with drug addicts, studies that characterized people integrated into treatment programs, intervention reports and expert opinion. Were analysed 32 articles, 2 monographs, thesis 2 and 5 institutional reports. The descriptors were: needs assessment, outcome, severity of addiction, quality of life. We researched data about people consuming over 35 years of age. The current study revealed the importance of three significant determinants for the health needs of drug users. The determinants are: the poly-substances; co-morbidities and aging consuming substances. The population that uses the services of specialized care and community intervention studies show an increasing polydrug use of different substances, show a significant percentage of physical and psychological co-morbidities, and the units are meeting with increasingly advanced age showing the perspective of chronic illness. It is these factors that will largely determine the health needs and will direct the practice of nursing. Many diagnoses materialize attention needs altered by these factors. Are related to physiological needs, psychosocial and psycho spiritual.